2018
DOI: 10.3390/w10121741
|View full text |Cite
|
Sign up to set email alerts
|

Head Loss Reduction in Surcharged Four-Way Junction Manholes

Abstract: Head loss in surcharged four-way junction manholes is a factor that increases damage due to urban inundation; thus, the flow characteristics of such manholes must be analyzed to reduce the head loss. In this study, a physical model was constructed; this model included a manhole and a connection pipe, fabricated on a 1/5 scale by applying sewer facility standards to perform a physical model investigation. Numerical simulations were performed using the Fluent model to derive efficient benching designs that can r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Moreover, the complex nature of flow is affected by an almost infinite variety of geometrical and hydraulic factors [14]. Some critical factors are the inflow rate, the shape of a manhole, surcharge condition, connecting pipe size, angle of connection, and manhole diameter ratios, among others [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the complex nature of flow is affected by an almost infinite variety of geometrical and hydraulic factors [14]. Some critical factors are the inflow rate, the shape of a manhole, surcharge condition, connecting pipe size, angle of connection, and manhole diameter ratios, among others [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Urban drainage systems are usually designed for stormwater events with a return period of 2-10 years, which usually consist of combined surface and underground infrastructures. The hydraulic performance of drainage structures such as street inlets, manholes and drop shafts, as well as sewer pipes, can affect the overall conveyance efficiency of the whole storm drainage system and also affect the flood inundation extent of streets and roadways during stormwater events (Chanson, 2004;Djordjević et al, 2005;León et al, 2010;Leandro and Martins, 2016;Kim et al, 2018). A detailed numerical model study of an urban flood occurring in a campus indicated that about 70% of the total stormwater volume was released from various street inlets into the underground drainage system (Liu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Results show that various parameters affect the hydraulic performance of the drop manhole. Kim et al (2018) used a physical model to derive efficient benching designs that can reduce head loss. Results indicate that the installation of full rectangular benching reduced the head loss coefficients and can be installed to improve the drainage capacity of urban stormwater conduit facilities.…”
Section: Introductionmentioning
confidence: 99%